Management of acute kidney injury associated with Covid-19: what have we learned?. Issue 6 (November 2021) - Cottam, Daniel; Nadim, Mitra K.; Forni, Lui G.
Abstract : Purpose of review: Although initially kidney involvement in COVID-19 infection was felt to occur relatively infrequently, this has proved not to be the case. In critically ill patients with COVID-19, multiorgan failure including acute kidney injury (AKI) is common and is associated with an increased risk of mortality and morbidity. This review focuses briefly on the epidemiology and pathophysiology of COVID-19 associated AKI as well as options for management. Recent findings: The risk factors for AKI are common to both noncovid-related AKI and COVID-19 associated AKI. Kidney injury in COVID-19 associated AKI may arise through several mechanisms, including not only direct effects on the kidney leading to tubular injury but also through the effects of treatment of multiorgan failure complicating infection. During surge conditions, the use of kidney replacement therapy has embraced all modalities including the use of peritoneal dialysis. The use of blood purification techniques has been proposed, but to date, the results are variable. Summary: COVID-19 associated AKI is common, affecting approximately a quarter of patients hospitalized with COVID-19. Glomerular injury can occur, but in the main tubular injury seems most likely leading to AKI, which should be managed following clinical pathways informed by accepted guidelines.